Preparation of graphene oxides with different sheet sizes by temperature control - 钱哲 陈亮 李德远 彭兵权 石国升 徐刚 方海平 吴明红 (Chinese physics B, 2017)
The sheet size of a graphene oxide （GO） can greatly influence its electrical, optical, mechanical, electrochemical and catalytic property. It is a key challenge to how to control the sheet size during its preparation in different application fields. According to our previous theoretical calculations of the effect of temperature on the oxidation process of graphene, we use Hummers method to prepare GOs with different sheet sizes by simply controlling the temperature condition in the process of the oxidation reaction of potassium permanganate （KMnO4） with graphene and the dilution process with deionized water. The results detected by transmission electron microscopy （TEM） and atomic force microscopy （AFM） show that the average sizes of GO sheets prepared at different temperatures are about 1 μm and 7 μm respectively. The ultraviolet-visible spectroscopy （UV-vis） shows that lower temperature can lead to smaller oxidation degrees of GO and less oxygen functional groups on the surface. In addition, we prepare GO membranes to test their mechanical strengths by ultrasonic waves, and we find that the strengths of the GO membranes prepared under low temperatures are considerably higher than those prepared under high temperatures, showing the high mechanical strengths of larger GO sheets. Our experimental results testify our previous theoretical calculations. Compared with the traditional centrifugal separation and chemical cutting method, the preparation process of GO by temperature control is simple and low-cost and also enables large-size synthesis. These findings develop a new method to control GO sheet sizes for large-scale potential applications.